Learning Style Tendencies of Early Adult Community Education Students Across Cohorts - Muhammad Irfan Hilmi; Jajat Sudrajat Ardiwinata; Deditiani Tri Indrianti; Sucianingsih Sucianingsih; Lutfi Ariefianto (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This study examines learning style tendencies among early adult Community Education students and compares their distribution across three cohorts. It responds to limited evidence on Kolb-informed experiential learning tendencies in community education, especially when such data are used for program-level pedagogical reflection rather than psychological labeling. A quantitative cross-sectional descriptive-comparative survey was conducted with total sampling of complete and valid responses from active students in the 2022, 2023, and 2024 cohorts (N = 210). An 18-item practical inventory, conceptually mapped to Kolb's experiential learning dimensions, classified tendencies into diverging, assimilating, accommodating, and converging. Data were analyzed using frequency distribution, cross-tabulation, chi-square test, and Cramer's V. Results showed that diverging was the most common tendency (34.8%), followed by assimilating (33.8%), accommodating (19.5%), and converging (11.9%). Cross-cohort differences were not statistically significant (χ²(6, N = 210) = 4.60, p = .596, V = .10). The findings indicate a stable reflective profile and support multimodal experiential pedagogy for classroom learning and community lab-site practice.